The Pershing Myth: Trump, Islamophobic Tweets, And The Construction Of Public Memory. - Ouassini, Anwar; Amini, Mostafa (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
One of the enduring narratives of the 2016 presidential election was the nostalgic journey President Trump took the American public on to construct his Islamophobic memory surrounding General Pershings actions during the American occupation of the Philippines. While the mobilization of memory by political actors is not new in Presidential elections, the mechanism utilized to impose and mobilize pubic memory was. This paper explores how the President Trumps tweets via the Twitter social media platform transform into mediated sites of contention in the nurturance of public nostalgia. As a public site that is visited by millions of people -the tweet not only memorializes events of the past but it mobilizes meaning, memory, and the societys sense of self, which has the ability to redirect and shape public memory. We argue that Trumps nostalgic colonial folklore via the tweet serves his ideological sentiments and larger political platforms in order to promote a vision of the past to provide his right-wing ideologies and movement supporters currency.